Coprological Examination of Ovine Fasciolosis in Horro District Community Based Sheep Breeding Program, Horro Guduru Wollega Zone, Western Ethiopia - Lule Bimirew, Fanta; Mersha Cherinnat, Tesfaye (Journal of Veterinary Healthcare, 2020)
A cross-sectional study was conducted from November 2017 to March 2018 to determine the prevalence of ovine fasciolosis in the Community Based Horro Sheep Breeding site at Horro district, Horro Guduru Wollega zone, Ethiopia. Coprological examination was performed on a total of 390 sheep at the study area. Age, sex, body condition score and peasant association were taken into consideration as rik factors. An overall prevalence of fasciolosis 45.4% 95% CI (40.41 50.36 was found on the basis of coprological examinations. The prevalence of fasciolosis findings according to PAs were (41.5%) in Laku Ingu and (48.2%) in Gitilo Dole. Statistical analysis of the prevalence among study site (PAs) showed insignificant difference P=0.102 (P>0.05), but significant difference (P<0.05) was observed between animal age groups (P=0.032, with a prevalence of 37.2% in young and 49.8% in adult) and body condition scores (P=0.001, with a prevalence of 57.9%, 43.5% and 29.9% in sheep with poor, medium and good body condition score, respectively. There was insignificance difference (P>0.05) in sex group of study animals in which the prevalence was 47.6% in female and 38.8% in male. Therefore further studies on the epidemiology, seasonal dynamic of the disease, the snail intermediate host and impacts of the infection in animal production with implementations of strategic intervention is necessary.
Keywords: Coprological examination; Horro district; Ovine fasciolosis; Prevalence; Risk factors